The road is made by walking : evaluating the implementation of a laboratory system - Ulriksen, Gro-Hilde (Universitetet i Tromsø, 2012)
This is an evaluation of implementing LabCraft to the Bloodbank at UNN Tromsø, based on a qualitative method, interviewing different users. Most challenges were directly or in- directly caused by the struggle between the top-down and the socio-technical approach. The topdown management-controlled approach used at hospitals where standardizations, cost saving and efficiency is key factors, is challenged by the socio-technical approach, based on user participation, and room for local adjustments to systems. The user role in the process directly influences the outcome of the process as well as the communication between the actors. More user participation in hospital implementations is needed, especially in the pre implementation phase. Detecting errors in the pre implementation phase prevents challenges later in the process. When creating demands for the tender all needed specifications must be included, to fit the Bloodbanks needs. All parts of the system must be included in the tender, also those working well. The installed base and the information infrastructure must be considered as well. Too close attachment to the old system may prevent users from seeing the improvements in the new system. Routines for conducting hospital implementations should be established as well as defining areas of responsibility for different actors.